Urine polymerase chain reaction as a screening tool for the detection of congenital cytomegalovirus infection. Issue 5 (1st September 2003) - Schlesinger, Y; Halle, D; Eidelman, A I; Reich, D; Dayan, D; Rudensky, B; Raveh, D; Branski, D; Kaplan, M; Shefer, V; Miron, D
Abstract : Objectives: To define the incidence of congenital cytomegalovirus (CMV) infection in a defined population in Israel as diagnosed by urine polymerase chain reaction (PCR), and to assess the utility of this method for screening for congenital CMV infection. Design: A convenient sample of urine specimens from asymptomatic newborns were subjected to CMV PCR. Positive results were validated by urine tube culture and by determination of serum CMV IgM antibodies. Maternal CMV IgG was determined in a representative sample of mothers. Newborns with positive urine specimens underwent full clinical evaluation. Epidemiological characteristics of the mothers were extracted from the medical records. Settings: Two medical centres in Israel with different population characteristics. Patients: A total of 2000 newborns (1000 in each medical centre). Main outcome measure: Presence of CMV DNA in the urine. Results: Despite significant epidemiological differences between the populations in the two hospitals, the CMV seroprevalence was similar, 80.5% and 85%. Fourteen of the 2000 newborns screened (0.7%) were PCR positive. Urine culture was positive in nine of 10 specimens; IgM was positive in only two of 13 newborns with positive PCR. Eleven newborns underwent full or partial evaluation, and only one (9%) was symptomatic. Conclusions: The incidence of congenital CMV infection in the study population was 0.7%; over 90% were asymptomatic. Urinary CMV PCR is a reliable, rapid, and convenient method, and thus may serve as a screening tool for the detection of congenital CMV infection.